Implementation outline of climate-smart one health: a system-thinking approach - Tepa-Yotto, G.; Tonnang, H. E. Z.; Yeboah, S.; Osae, M. Y.; Gariba, A. A.; Dalaa, M. A.; Obeng Adomaa, F.; Damba, O. T.; Kyere, R.; Moutouama, F. T; Agboton, C.; Winsou, J. K.; et al. (MDPI, 2024)
The One Health (OH) concept has evolved significantly in recent decades, emerging as a key framework guiding international research and policy in managing new infectious diseases, chiefly zoonoses. While its initial conception revolved around managing zoonotic diseases as they traverse the interface between animals and humans through the environment, this concept has transformed beyond its origins as a collaboration solely between veterinary and public health stakeholders. Notably, the past decade has ushered in a new era of addressing complex issues in a novel manner. Emerging evidence has led to a fresh theoretical framework, highlighting interconnected terrestrial and aquatic ecosystems. Understanding these links is crucial in tackling emerging issues and resultant health challenges within these systems under what we call One Health 2.0. The current paper describes Climate-Smart One Health (CS-OH) and Climate-Smart Integrated Pest Management (CS-IPM) approaches, emphasizing holistic perspectives and practical tools. The One Health (OH) 2.0 concept applies to the agricultural sector and more specifically to agrifood systems exposed to climate change impacts. It is meant to address, in a comprehensive manner, soil, water, plant, animal, rural and urban farmers and farming communities, and consumer health issues. The One Health (OH) 2.0 concept is embodied in the Climate-Smart One Health (CS-OH) approach. The latter is designed for applications in agrifood systems. Pathways for the deployment of both CS-OH and CS-IPM interventions are proposed in this paper. A Ghanaian case is discussed.